COVID-19 Vaccination, Peltzman Effect and Possible Increase in Highrisk Behaviors: A Growing Concern Related to Risk Compensation and Reduced Compliance to Public Health Protective Measures after Vaccines Rollout - Falahi, Shahab; Mohamadi, Jasem; Sayyadi, Hojjat; Pakzad, Iraj; Rashidi, Ayoub; Naserifar, Razi; Abdi, Jahangir; Kenarkoohi, Azra (Infectious Disorders - Drug Targets, 2022)
The world is still faced with widespread dissemination and many unanswered questions related to Coronavirus disease (COVID-19). Several candidate vaccines have been introduced against COVID-19, mostly requiring the injection of two doses and some with nearly 90-95% efficacy. All strategies against the spread of infection have focused on breaking the chain of virus transmission through protective public health measures and mass vaccination. The current situation emphasizes the global need for carefully designed policies to maximize vaccine access and uptake. The risk compensation theory (Peltzman Effect) states that the decrease in perceived risk through access to preventive measures may lead to increasing frequency of risky behaviors. The current pandemic has exposed people to the sense of risk compensation and behavior change in response to the perceived risk. Risk compensation phenomenon may significantly reverse the benefits of COVID-19 vaccination, especially if the vaccine is not sufficiently effective in real life or among high-risk populations. Recognition and awareness of Peltzman risk compensation are of high importance in counteracting and neutralizing the false complacency of the community, which also lends more weight to public health efforts. The public health messages and practices should be clearly expressed, straightforward, reliable and applicable. It is important to encourage mass vaccination of the population, and other NPIs must be re-established and implemented to ensure education to live with COVID-19 in parallel with daily activities and job tasks.
Keywords: vaccination